Pain thresholds and suprathreshold pain after sleep restriction in migraine – A blinded crossover study. (May 2022) - Neverdahl, Jan Petter; Uglem, Martin; Matre, Dagfinn; Hansen, Johannes Orvin; Engstrøm, Morten; Tronvik, Erling; Stovner, Lars Jacob; Sand, Trond; Omland, Petter Moe
Objective: There is an unexplained association between disturbed sleep and migraine. In this blinded crossover study, we investigate if experimental sleep restriction has a different effect on pain thresholds and suprathreshold pain in interictal migraineurs and controls. Methods: Forearm heat pain thresholds and tolerance thresholds, and trapezius pressure pain thresholds and suprathreshold pain were measured in 39 interictal migraineurs and 31 healthy controls after two consecutive nights of partial sleep restriction and after habitual sleep. Results: The effect of sleep restriction was not significantly different between interictal migraineurs and controls in the primary analyses. Pressure pain thresholds tended to be lower (i.e., increased pain sensitivity) after sleep restriction in interictal migraineurs compared to controls with a 48-hour preictal-interictal cut-off (p = 0.061). We found decreased pain thresholds after sleep restriction in two of seven migraine subgroup comparisons: heat pain thresholds decreased in migraineurs with lower pain intensity during attacks (p = 0.005) and pressure pain thresholds decreased in migraineurs with higher severity of photophobia during attacks (p = 0.031). Heat pain thresholds tended to decrease after sleep restriction in sleep-related migraine (p = 0.060). Sleep restriction did not affect suprathreshold pain measurements in either group. Conclusion: This study could not provide strong evidence for an increased effect of sleep restriction on pain sensitivity in migraineurs compared to healthy controls. There might be a slightly increased effect of sleep restriction in migraineurs, detectable using large samples or more pronounced in certain migraine subgroups.